Risk stratification in acute coronary syndrome: Evaluation of the GRACE and CRUSADE scores in the setting of a tertiary care centre. Issue 2 (22nd November 2019) - Tscherny, Katharina; Kienbacher, Calvin; Fuhrmann, Verena; van Tulder, Raphael; Schreiber, Wolfgang; Herkner, Harald; Roth, Dominik
Abstract: Objective: Risk assessment plays a decisive role in the management of acute coronary syndrome (ACS). The GRACE and the CRUSADE scores are among the most frequently used risk assessment tools. We aimed to compare the performance of the GRACE and CRUSADE risk scores to predict in‐hospital mortality and major bleeding in a contemporary ACS population at a high‐volume academic hospital. Methods: All patients treated for ACS from January 1, 2006 to December 31, 2015 at a tertiary care centre were prospectively enrolled. We calculated GRACE and CRUSADE risk scores. We compared the discrimination capacity of both scores for in‐hospital mortality and major bleeding. Results: In total 4087 patients (1151 [28.2%] female; age 62 ± 14 years) were included. Among these 2218 (54.3%) were diagnosed with ST‐elevation myocardial infarction, 113 (2.8%) died in hospital and major bleeding occurred in 65 (1.6%). Discrimination capacity for in‐hospital mortality of the GRACE score was superior to the CRUSADE score (receiver operator characteristic area under the curve (AUC) 0.91 (95% CI 0.89‐0.93) vs 0.83 (95% CI 0.80‐0.86); P  < .01). Performance for major bleeding differed but was poor for both scores (AUC 0.71 [0.65‐0.76] for GRACE vs 0.61 [0.55‐0.68] for CRUSADE; P  < .01). Conclusion: The GRACE score appears to be superior over CRUSADE to predict in‐hospital mortality. Major bleeding is rare in the era of primary PCI and performance of both scores for this outcome was poor.